2019
DOI: 10.1002/acm2.12731
|View full text |Cite
|
Sign up to set email alerts
|

The ideal couch tracking system—Requirements and evaluation of current systems

Abstract: Introduction: Intrafractional motion can cause substantial uncertainty in precision radiotherapy. Traditionally, the target volume is defined to be sufficiently large to cover the tumor in every position. With the robotic treatment couch, a real-time motion compensation can improve tumor coverage and organ at risk sparing. However, this approach poses additional requirements, which are systematically developed and which allow the ideal robotic couch to be specified.Methods and materials: Data of intrafractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Still, Jöhl et al found acceptable levels of stress in healthy participants [52]. The authors also studied requirements on the accuracy and dynamic properties for robotic couches to enable motion compensation and evaluated several commercially available models [53]. The idea to actively move the patient to align the target with the beam has also been studied in the context of cranial RS using conventional gantry based LINACs [19].…”
Section: Robotic Patient Positioningmentioning
confidence: 99%
“…Still, Jöhl et al found acceptable levels of stress in healthy participants [52]. The authors also studied requirements on the accuracy and dynamic properties for robotic couches to enable motion compensation and evaluated several commercially available models [53]. The idea to actively move the patient to align the target with the beam has also been studied in the context of cranial RS using conventional gantry based LINACs [19].…”
Section: Robotic Patient Positioningmentioning
confidence: 99%
“…Pommer et al conclusion corroborate the data shown in figure 3 where the AP graphs show a cluster of errors plateauing at approximately 2.5 mm, corresponding to half of a leaf width. As an alternative to implementing thinner leaves, couch tracking (Jöhl et al 2019) could also help reduce residual uncertainties due to leaf width. Ehrbar et al (2017) showed that couch tracking alleviates the impact of the leaf width on the beam-surrogate tracking uncertainty.…”
mentioning
confidence: 99%
“…The use of multimodality imaging, such as PET/CT or PET/MRI (Pommer et al 2013), has been shown to improve delineation accuracy. The emergence of automatic or semi-automatic target segmentation (Pommer et al 2013, Ehrbar et al 2017, Jöhl et al 2019 is also showing promise to reduce the inter-observer variability while also potentially saving time for the clinician (Oar et al 2019).…”
mentioning
confidence: 99%